Acúmulo e disponibilidade de cromo, cádmio e chumbo em solos tratados com lodo de esgoto por onze anos consecutivos - de Macedo, Fernando Giovannetti (2012)
The sewage sludge used for agricultural purposes provides many benefits to soil, but it contain harmful elements to environment, that infers in a great attention on its use. The aim of this work was to evaluate the effects of successive applications of sewage sludge on heavy metals accumulation (cadmium, chromium and lead) in samples of soils and corn plants, as well as evaluate the chemicals extractants efficiency in estimate the phyto disponibility of those elements. The experiment was conducted in randomized blocks design in the 2007/08 season, with 4 treatments (0, 5, 10 and 20 Mg ha-1 of sewage sludge) and 5 replicates. It was evaluated: the quantities available of Cd, Cr and Pb in soil by Melich-1, Melich-3 and DTPA extractants; the quantities extracted by corn plants; and the correlation between the disposition and quantities of those metals on whole plants, diagnosis leaves and corn grains. The application of sewage sludge for eleven consecutive years has not showed increase in total quantity nor availability of Cr, Cd and Pb in the evaluated soils. The extractor Melich-1 was the only one that showed significant correlation for availability of Cd, Cr and Pb in soil and corn plants. The correlation of metal availability in soil x leaf diagnosis was significant only for Pb with the Melich-3 and DTPA extractants